2020
DOI: 10.1097/cm9.0000000000000747
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine-like factor-like MARVEL transmembrane domain-containing family in autoimmune diseases

Abstract: The chemokine-like factor (CKLF)-like MARVEL transmembrane domain-containing family (CMTM) is widely expressed in the immune system. Abnormal expression of CMTM is associated with the development of various diseases. This article summarizes the relevant research on the role of the CMTM family in immune disorders. This information will increase our understanding of pathogenesis and identify promising targets for the diagnosis and treatment of autoimmune diseases. The CMTM family is highly expressed in periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…CMKLR1 reportedly relieved allergic airway in ammation of asthma patients 28 . CMTM2, which belongs to the CMTM family, is highly expressed in peripheral blood mononuclear cells and is associated with numerous autoimmune diseases 29 . Neureg-ulin-1 (NRG-1), which is a member of the NRG gene family, acts as a paracrine factor in dendritic cells and is involved in tumor immunity 30 .…”
Section: Discussionmentioning
confidence: 99%
“…CMKLR1 reportedly relieved allergic airway in ammation of asthma patients 28 . CMTM2, which belongs to the CMTM family, is highly expressed in peripheral blood mononuclear cells and is associated with numerous autoimmune diseases 29 . Neureg-ulin-1 (NRG-1), which is a member of the NRG gene family, acts as a paracrine factor in dendritic cells and is involved in tumor immunity 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The structural characteristics of the encoded proteins of the CMTM family have similarities with those of chemokines and transmembrane-4 superfamily (TM4SF) members. Previous research showed that CMTM family members may have involvement in the progression of autoimmune (2) and cardiovascular diseases (3). Besides, mounting studies have pointed toward CMTM family members being pivotal players in tumor-related biological processes (BP).…”
Section: Introductionmentioning
confidence: 99%
“…The CMTM family was first cloned and reported in 2001 1 . To date, CMTM family members have been revealed to function as regulators in various diseases, including autoimmune 2 and cardiovascular diseases 3 . Moreover, recent in-depth studies have indicated that CMTMs also play crucial roles in cancer-associated biological regulation.…”
Section: Introductionmentioning
confidence: 99%